Modulation of neuronal firing mode in cat and guinea pig LGNd by histamine: possible cellular mechanisms of histaminergic control of arousal - McCormick, DA (J Neurosci, 1991)
The thalamus is innervated by histaminergic fibers presumably arising from neurons in the tuberomammillary nucleus of the hypothalamus. The possible function of this histaminergic projection was addressed through investigation of the cellular actions of histamine on guinea pig and cat dorsal lateral geniculate (LGNd) relay neurons maintained as a slice in vitro. Local application of histamine to LGNd relay neurons resulted in a slow depolarization that was associated with a decrease in membrane conductance and was blocked by the H1-antagonists pyrilamine, triprolidine, or diphenhydramine. Current versus voltage relationships revealed that the slow depolarization was associated with an inward current that reversed near EK, indicating that it was due to a decrease in a potassium current. The slow depolarizing response to histamine was occluded by maximal activation of the slow depolarizing responses resulting from stimulation of alpha 1-adrenergic or muscarinic receptors, suggesting that they are all mediated by reduction in the same potassium current and/or alteration of a common second messenger. In the presence of H1-receptor antagonists, application of histamine resulted in a small depolarization that was associated with a marked increase in apparent membrane conductance. Voltage-clamp recordings revealed that this response was associated with enhancement of the hyperpolarization-activated cation current Ih. This response to histamine was blocked by local or bath application of the H2-antagonists cimetidine or tiotidine. The functional consequences of these actions of histamine were addressed with extracellular and intracellular recordings in guinea pig and cat LGNd relay neurons. Extracellular recordings in cat LGNd revealed the occurrence of highly regular 1-4 Hz rhythmic burst discharges. Application of histamine halted rhythmic bursting and replaced it with a prolonged period of single-spike activity. Intracellular recordings indicate that the histamine-induced switch in firing mode is due largely to the slow depolarizing response mediated by H1-receptors, but is also facilitated by the enhancement of Ih mediated by H2-receptors. These postsynaptic actions indicate that increased activity in the tuberomammillary histaminergic system may result in a switch of thalamic neuronal activity from rhythmic burst firing to single-spike activity and thereby promote the accurate transmission and processing of sensory information and cognition.